Analisis Kepuasan Pelanggan terhadap Kualitas Pelayanan Jasa Ekspedisi dengan Metode Servqual dan Data Envelopment Analysis (DEA) di Kota Meulaboh - Saputra, Arie; Sofiyanurriyanti, Sofiyanurriyanti (Jurnal Sistem Teknik Industri, 2021)
Assessment of service performance is important for the sustainability and existence of the company in the market. Objective performance measurement can be done to see the internal strength of the company and can also show how the company competes with companies that cover the same area. J&T Express Meulaboh, which is a shipping service company in Meulaboh City, has never measured customer satisfaction, the management considers the services provided to be quite good, seen from visitors who use their services. An assessment of the company's performance has not been carried out so that it is not maintained whether it has used its resources efficiently and optimally. Measurement of company service performance is carried out using the Service Quality (Servqual) method to measure the level of customer satisfaction and the Data Envelopment Analysis (DEA) method to measure the company's efficiency value. The result of the 5 servqual gap calculation shows that all service quality attributes owned by J&T Express Meulaboh are negative, which indicates that J&T Express service performance has not met the expectations of customers who use its services. The results of calculations using the DEA method show that J&T Express Meulaboh is quite good and efficient with an efficient value of 1.